2017
DOI: 10.1007/s11356-017-9289-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different sewage sludge amendment rates on the heavy metal bioaccumulation, growth and biomass of cucumbers (Cucumis sativus L.)

Abstract: When sewage sludge is incorrectly applied, it may adversely impact agro-system productivity. Thus, this study addresses the reaction of Cucumis sativus L. (cucumber) to different amendment rates (0, 10, 20, 30, 40 and 50 g kg) of sewage sludge in a greenhouse pot experiment, in which the plant growth, heavy metal uptake and biomass were evaluated. A randomized complete block design with six treatments and six replications was used as the experimental design. The soil electrical conductivity, organic matter and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 52 publications
8
43
1
1
Order By: Relevance
“…In our investigation, soil OM increased with the rate of SS addition, achieving its greatest value with the maximum dose (150 t/ha). Eid, El‐Bebany, et al., ; Eid, Alrumman, et al., verified that the addition of SS to soil cultivated with spinach and cucumber promoted a rise in the soil content of OM. The soil OM content in nonamended soil was 1.3%, compared to 1.6, 1.7, 1.9, 2.1, and 2.4%, which corresponded to 1.2‐, 1.3‐, 1.5‐, 1.6‐, and 1.9‐fold increases, respectively, at 30, 60, 90, 120, and 150 t/ha SS amendment rates.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In our investigation, soil OM increased with the rate of SS addition, achieving its greatest value with the maximum dose (150 t/ha). Eid, El‐Bebany, et al., ; Eid, Alrumman, et al., verified that the addition of SS to soil cultivated with spinach and cucumber promoted a rise in the soil content of OM. The soil OM content in nonamended soil was 1.3%, compared to 1.6, 1.7, 1.9, 2.1, and 2.4%, which corresponded to 1.2‐, 1.3‐, 1.5‐, 1.6‐, and 1.9‐fold increases, respectively, at 30, 60, 90, 120, and 150 t/ha SS amendment rates.…”
Section: Discussionmentioning
confidence: 96%
“…However, SS may contain high levels of pollutants, either organic and/or HMs (Rastetter & Gerhardt, ). Therefore, an eco‐friendly management strategy of SS is required (Eid, Alrumman, et al., ) because it may lead to environmental pollution if not dealt with appropriately (Singh & Agrawal, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eljarrat et al (2008) reported the significant content of Polybrominated diphenyl ethers (PBDE) in sewage sludge ranged from 197 to 1185 ng/g dry weight (dw) and further in the sewage sludge amended soil PBDE levels in soils ranged between 21 and 690 ng/g dw. Moreover, levels about 200 ng/g dw have been reported in Eid et al (2017) sludge from Sweden and The Netherlands (Sellstrom et al, 1999;de Boer et al, 2002), and around 500 ng/g dw for samples collected in Denmark (Christenson et al, 2003). Higher concentrations were found in USA, with values ranging from 1000 to 2290 ng/g dm for tri-to hexa-BDEs, and from 85 to 4890 ng/g dm for deca-BDE-209, with the mean values of approximately 1600 and 1000 ng/g, respectively (Hale et al, 2003).…”
Section: Constraintsmentioning
confidence: 98%